Gene-diet interactions on plasma lipid levels in the Inuit population - Abdous, Belkacem; Rudkowska, Iwona; Hegele, Robert A.; Dewailly, Éric; Boiteau, Véronique; Vohl, Marie-Claude; Dubé-Linteau, Ariane; Giguère, Yves; Chateau-Degat, Marie-Ludivine (British Journal of Nutrition, 2020)
The Inuit population is often described as being protected against CVD due to their traditional dietary patterns and their unique genetic background. The objective of the present study was to examine gene–diet interaction effects on plasma lipid levels in the Inuit population. Data from the Qanuippitaa Nunavik Health Survey (n 553) were analysed via regression models which included the following: genotypes for thirty-five known polymorphisms (SNP) from twenty genes related to lipid metabolism; dietary fat intake including total fat (TotFat) and saturated fat (SatFat) estimated from a FFQ; plasma lipid levels, namely total cholesterol (TC), LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C) and TAG. The results demonstrate that allele frequencies were different in the Inuit population compared with the Caucasian population. Further, seven SNP (APOA1 − 75G/A (rs670), APOB XbAI (rs693), AGT M235T (rs699), LIPC 480C/T (rs1800588), APOA1 84T/C (rs5070), PPARG2 − 618C/G (rs10865710) and APOE 219G/T (rs405509)) in interaction with TotFat and SatFat were significantly associated with one or two plasma lipid parameters. Another four SNP (APOC3 3238C>G (rs5128), CETP I405V (rs5882), CYP1A1 A4889G (rs1048943) and ABCA1 Arg219Lys (rs2230806)) in interaction with either TotFat or SatFat intake were significantly associated with one plasma lipid variable. Further, an additive effect of these SNP in interaction with TotFat or SatFat intake was significantly associated with higher TC, LDL-C or TAG levels, as well as with lower HDL-C levels. In conclusion, the present study supports the notion that gene–diet interactions play an important role in modifying plasma lipid levels in the Inuit population.